PENINGKATAN HASIL BELAJAR PESERTA DIDIK MENGGUNAKAN MODEL KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) BERBANTUAN MEDIA PUZZLE PEMBELAJARAN PENDIDIKAN PANCASILA KELAS V SDN 15 ULU GADUT - Asmi, Annisa; Waldi, Atri; Safitri, Serly; Reinita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low learning outcomes of students in Pancasila Education due to the suboptimal use of models and media. This study aims to describe the improvement in student learning outcomes using the Teams Games Tournament (TGT) Cooperative Model assisted by Puzzle Media in Grade V of SDN 15 Ulu Gadut. This research is a Classroom Action Research (CAR) with a qualitative and quantitative approach. This research was conducted in two cycles, each cycle consisting of planning, implementation, observation, and reflection. The research subjects were teachers and students in Grade V of SDN 15 Ulu Gadut, Padang City, consisting of 26 students, comprising 12 male students and 14 female students. The results of the study showed an increase in several aspects, namely: a) lesson plans from 87.49% (Good) in cycle I to 94.44% (Very Good) in cycle II, b) teacher activity from 85.71% (Good) in cycle I to 92.85% (Very Good) in cycle II, c) student activity from 85.71% (Good) in cycle I to 92.85% (Very Good) in cycle II, and d) learning outcomes increased from 81.17% (Good) in cycle I to 91.18% (Very Good) in cycle II. Therefore, the use of the Teams Games Tournament (TGT) cooperative model assisted by puzzle media has been proven to improve learning outcomes in Pancasila Education.